Proposed Application of Taguchi Methods to Pymes - Cevallos Ampuero, Juan (2000)
This article aims at presenting a proposal to apply the Taguchi methods in improving production processes of small and medium enterprises. The theoretical framework for a methodology that has been simplified, elsewhere the application of case studies will be presented this opportunity presents